Assessment of the bone thickness of the palate on cone-beam computed tomography for placement of miniscrew-assisted rapid palatal expansion appliances - Negrisoli, Silvia; Angelieri, Fernanda; Gonçalves, João Roberto [UNESP]; da Silva, Hélio Doyle Pereira; Maltagliati, Liliana Ávila; Raphaelli Nahás-Scocate, Ana Carla (Elsevier, 2022)
Introduction: The correction of maxillary transverse discrepancy is achieved by means of rapid maxillary expansion, which may be performed by conventional or surgically-assisted rapid maxillary expansion, and more recently, by miniscrew-assisted rapid palatal expansion (MARPE). This study assessed the bone thickness of the palate on cone-beam computed tomography (CBCT) images for placement of mini-implants and anchorage of MARPE. Methods: The sample consisted of 223 CBCT scans from patients of both genders (137 females and 86 males) aged ≥18 years. By using the Image Studio software (Anne Solutions, São Paulo, Brazil), measurements of the bone thickness of the palate were performed bilaterally, as follows: in the axial plane, the bone thicknesses were determined in the anterior region (distal face of the first premolars) and the posterior region (distal face of the first molars), at 3 mm and 6 mm laterally to the midpalatal suture. So in the sagittal plane, the bone thicknesses of the palate were measured in these placements from the palatal cortical to the nasal floor cortical in the anterior region at 30°, 45°, and 90°. In the posterior region, the bone thickness was determined only at 90°. The statistical tests used were the Kruskal-Wallis H test (analysis of variance on ranks) with Dunn's post-hoc test and Mann-Whitney U test (P <0.05). Results: The bone thickness of the palate in the anterior region varied from 8.57 mm in women to 11.28 mm in men at 3 mm from the midpalatal suture and from 7.99 mm in women to 10.47 mm in men at 6 mm for 30°; from 6.35 mm in women to 9.28 mm in men at 3 mm from the midpalatal suture and from 6.20 mm in women to 8.88 mm in men at 6 mm for 45°; from 4.51 mm in women to 6.85 mm in men at 3 mm from the midpalatal suture and from 4.29 mm in women to 6.64 mm in men at 6 mm for 90°. In the posterior region, the bone thickness varied from 2.93 mm (3 mm from the suture) to 1.78 mm (6 mm from the suture) for women and from 3.24 mm (3 mm from the suture) to 1.99 mm (6 mm from the suture) for men. In general, the bone thickness of the palate is greater in the anterior region at 3 mm from the midpalatal suture at 30°. Conclusions: There was high variability in the bone thickness of the palate among patients and in different areas. Therefore, it is necessary to make an individualized diagnosis of the patient and manufacture the MARPE appliance carefully by performing a prior evaluation of the palatal bone thickness by means of CBCT to determine the ideal sites and inclinations for placement of mini-implants.